Integrated Sexual Reproductive Health Information, Education And Communication (IEC) Can Increase Couple Compliance With Prospective Bridge In Health Examination In Pontianak City - Eka Santy; Riska Regia Catur Putri; Lydia Febri Kurniatin (Journal of Midwifery, 2022)
Background: Cases of maternal mortality and HIV/AIDS in West Kalimantan tend to increase. Every couple needs pregnancy planning so that the mother and baby are born healthy. One of the efforts is the Information, Education and Communication (IEC) program on Reproductive Health, Sexual and Health Examination for Prospective Brides, to prepare couples in a healthy condition.Research Objectives: To determine the implementation and effectiveness of IEC for Reproductive, Sexual Health and Health Examination of Future Brides and Grooms in Pontianak City.Research Methods: This research uses Mixed Methods. Qualitative design is descriptive. Data collection through FGD and interviews with key informants. The quantitative design is an analytical survey. Collecting data using a questionnaire, on 90 Future Bride and Groom taken by purposive sampling.Qualitative Research Results: Executors are adequate and have received training. Flipcharts and posters are available, pocket books have not been fulfilled. Limited supporting facilities. There is an MoU with the KUA, but not yet with the blessing of other religions. Limited delivery time. Materials on nutrition and the husband's role are still few, and there is no environmental health material. 95% future brides and grooms do health check.Quantitative Results The perception of the implementation of IEC showed a significant relationship with the compliance of respondents in the health examination (p = 0.009; OR=4.4).Conclusion: Implementation of IEC for Reproductive Health, Sexual and Health Examination in Future Brides and Grooms is running and effective. Perceptions of the implementation of IEC showed a significant relationship with the compliance of respondents in conducting health checks